2014
DOI: 10.1007/s10903-014-0011-1
|View full text |Cite
|
Sign up to set email alerts
|

International Migration from Non-endemic Settings as a Protective Factor for HIV/STI Risk Among Female Sex Workers in Vancouver, Canada

Abstract: Background Given heterogeneous evidence regarding the impacts of migration on HIV/sexually transmitted infections (STIs) among female sex workers (FSWs), we explored factors associated with international migration among FSWs in Vancouver, Canada. Methods We draw on baseline questionnaire and HIV/STI testing data from a community-based cohort, AESHA, from 2010-2012. Logistic regression identified correlates of international migration. Results Of 650 FSWs, 163 (25.1%) were international migrants, who primari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 57 publications
7
37
0
Order By: Relevance
“…Among im/migrant SWs, these inequities may be magnified by macrostructural determinants related to sex work, including stigma, discrimination, and criminalization of sex work (Goldenberg, Liu, et al, 2014; Kate Shannon et al, 2014). Specifically, institutional barriers that may affect obtainment of health services for im/migrant SWs include fear of disclosing sex work to health providers, foregoing care in order to continue earning income, denial or delay of public health insurance, high cost of private health insurance, and ineligibility for social assistance and subsidized housing (Anderson et al, 2015; Goldenberg, Duff, & Krusi, 2015; Oxman-Martinez et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among im/migrant SWs, these inequities may be magnified by macrostructural determinants related to sex work, including stigma, discrimination, and criminalization of sex work (Goldenberg, Liu, et al, 2014; Kate Shannon et al, 2014). Specifically, institutional barriers that may affect obtainment of health services for im/migrant SWs include fear of disclosing sex work to health providers, foregoing care in order to continue earning income, denial or delay of public health insurance, high cost of private health insurance, and ineligibility for social assistance and subsidized housing (Anderson et al, 2015; Goldenberg, Duff, & Krusi, 2015; Oxman-Martinez et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Women are migrating for purposes of seeking new economic and social opportunities, family reunification, and improved health and security (Goldenberg, Liu, Nguyen, Chettiar, & Shannon, 2014; Platt et al, 2013; Zimmerman, Kiss, & Hossain, 2011). However, resettlement in destination countries often results in a number of barriers to health for women including language barriers, discrimination, and limited access to services; and migrant women are consequently disproportionately represented within precarious forms of work, including sex work (Goldenberg, 2016; MacDonnell, Dastjerdi, Khanlou, Bokore, & Tharao, 2016).…”
mentioning
confidence: 99%
“…Participants of Aboriginal ancestry have been shown to experience heightened violence, and as such were included in the model a priori . A binary variable was developed to control for migration by comparing those born in Canada to new migrants(Goldenberg, Liu, Nguyen, Chettiar, & Shannon, 2014). To account for experiencing violence at multiple points along the lifespan (Ulibarri et al, 2010), childhood trauma was included as a confounder and defined as experiencing emotional, physical or sexual trauma before the age of 18 years.…”
Section: Methodsmentioning
confidence: 99%
“…However, research suggests diversity in the health impacts of migration, which can foster exposure to enhanced risks (e.g., drug use, violence, loss of social support) as well as protective factors such as better wages and working conditions 1,35 . For example, a recent systematic review comparing HIV and STI prevalence among migrant and non-migrant female SWs found that while migrants in low- and high-income countries faced increased STI prevalence in all countries compared to non-migrants, only those in lower-income countries were also at elevated risks of HIV 1 .…”
Section: Introductionmentioning
confidence: 99%